Synthesis of high-entropy diboride TiZrNbHfTaB2 by vacuum-free direct current arc plasma method; International Journal of Refractory Metals and Hard Materials; Vol. 134 - Pak A. Ya. Aleksandr Yakovlevich; Povalyaev P. V. Pavel Vadimovich; Vlasov A, V. Aleksey Vladimirovich; Gerasimov R. D. Roman Dmitrievich; Bolatova Zh. S. Zhanar Sanatovna; Svinukhova A. A. Arina Andreevna; Spodina A. V. Anastasiya Vyacheslavovna; Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna (2026, 2026)
Title screen